Nanoemulsion as a Platform for Iontophoretic Delivery of Lipophilic Drugs in Skin Tumors - Luciana Facco Dalmolin; Renata F. V. Lopez (MDPI AG, 2018)
Lipophilic drugs do not usually benefit from iontophoresis mainly because they do not solubilize in aqueous formulations suitable for the application of electric current. To explore the influence of iontophoresis on penetration of these drugs, a cationic nanoemulsion was developed to solubilize zinc phthalocyanine (ZnPc), a promising drug for the treatment of skin cancer. To verify the influence of particle size on iontophoresis, an emulsion of nanoemulsion-like composition was also developed. The formulations were characterized and cutaneous and tumor penetration studies were performed in vitro and in vivo, respectively. With particles of about 200 nm, the nanoemulsion solubilized 2.5-fold more ZnPc than the 13-µm emulsion. At the same concentration of ZnPc, in vitro passive penetration studies showed that the nanoemulsion increased, after 1 h of treatment, by almost 4 times the penetration of ZnPc into the viable layers of the skin when compared to the emulsion, whereas iontophoresis of nanoemulsion resulted in a 16-fold increase in ZnPc penetration in only 30 min. An in vivo study in a murine model of melanoma showed that ZnPc reached the tumor after iontophoresis of the nanoemulsion. Therefore, iontophoresis of nanoemulsions appears to be a promising strategy for the topical treatment of tumors with lipophilic drugs.